The urban development of Kazimierz Dolny in the Middle Ages from documentary and archaeological sources - Lis, Paweł; Pisarek, Katarzyna (Institute of Archaeology Rzeszów University, 2012)
Medieval settlement in Kazimierz Dolny, a property of the prince, was originated in the middle of the thirteenth century after disappearance of the nunnery of Kazimierz, located on the hill where the castle was built later. On Góra Wietrzna (Windy Hill), after the transfer of ‘Skowieszyn key’ to monastery in Zwierzyniec, there was a Norbertine settlement. The prince’s settlement Kazimierz had a convenient location near the crossing of Vistula and Grodarz rivers, on a place safe from flooding. On the slope of the hill there could have been a post-monastic church, which presumably was soon converted into the parish church, and at the top was the tower, which guarded the crossing and was the seat of the prince of the settlement.
Rozwój przestrzeni miejskiej Kazimierza Dolnego w średniowieczu w świetle źródeł pisanych i źródeł archeologicznych
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, medieval; Kazimierz Dolny; Skowieszyn; Wietrzna Góra; "Skowieszyn key"; prince's settlement